A Study on Treatment of Love in Ruskin Bond Stories: Exploring the Treatment of Love in Ruskin Bond Stories (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Love is an emotion that has prevailed from time immemorial in global literature and it is not true that this feeling is our sole motive force. It is in contemporary writing now and there it was in ancient literature. Love doesn't recognize limits and can never be limited to human shackles. It is free and a loving person touches the spike of everlasting love which remains unknown to him. Love may be understood in many ways, but the fundamental element never changes. In this study, we have discussed the treatment of love in Ruskin Bond stories.